Avian determinants of rocky intertidal community structure in South Africa - Bosman, Alison L (University of Cape Town, 2014)
Includes bibliographies. === Rocky islands in Saldanha Bay, southwestern Cape, South Africa, support aggregations of seabirds. Guano produced by the seabirds washed off the islands into intertidal and nearshore waters,where it provides a source of inorganic and organic nutrients. The concentrations of nutrients in intertidal rockpools at island and mainland sites in the Saldanha Bay area were measured,and the biological structures of intertidal communities at these sites were compared in the light of differences in intertidal nutrient status. Monthly measurements were made of algal production and of the growth, density, reproductive condition and mortality of the dominant intertidal herbivore, Patella granularis.The rate of intertidal algal production was enhanced on shores washed by nutrient-rich waters, and the growth rates and life-history patterns of populations of P. granularis were, in turn, modified by the increased availability of algal food. On unenriched shores rates of algal production and limpet growth and reproduction were slow. Seabirds thus influence trophic relationships between intertidal organisms, without themselves being components of the community. Islands in Saldanha Bay also support dense populations of African Black Oystercatchers Haematopus moqu.ini, which forage intertidally. Predation by oystercatchers on P. granular is resulted in a modification of limpet densities and population size structures, and a reduction in the intensity of grazing. The impact of predation was, however, modified by the presence, in intertidal waters, of nutrients from seabird guano, and the consequences thereof. It is proposed that differences in the structures of communities on rocky shores, and in the roles of processes influencing structure, might •be due, in part, to differences in the nutrient status of intertidal waters.